2022
DOI: 10.1155/2022/8230212
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Effect of CT‐Guided Artificial Pneumothorax plus Thoracoscopy and Central Venous Catheterization on the Drainage Effect of Pediatric Empyema and Pulmonary Function

Abstract: The aim of the study is to investigate the effect of CT-guided artificial pneumothorax combined with a thoracoscopic and central venous catheter on empyema drainage effect and pulmonary function in children. A total of 82 pediatric patients with empyema admitted to our hospital from January 2020 to December 2021 were retrospectively analyzed. The control group was treated with artificial pneumothorax combined with thoracoscopy. The study group was treated with a CT-guided and central venous catheter. The opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…FVC, FEV 1 , and FEV 1 /FVC are the most common indicators in the studies on the influencing factors of lung function, which can better reflect lung ventilation function. FVC can reflect the expiratory resistance of large airways (16). FEV 1 is the main indicator of impaired lung function (17).…”
mentioning
confidence: 99%
“…FVC, FEV 1 , and FEV 1 /FVC are the most common indicators in the studies on the influencing factors of lung function, which can better reflect lung ventilation function. FVC can reflect the expiratory resistance of large airways (16). FEV 1 is the main indicator of impaired lung function (17).…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%